Sharing information to protect forests - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2005)
Forests face a number of natural threats, including fire, insects and diseases. This edition of Unasylva, FAO s journal on forestry issues and industries, takes a look at some of the measures taken to protect forests, and the progress made so far in pro